Oracle SQL Recipes: A Problem-Solution Approach - Allen, Grant (Apress, 2012)
Welcome to Oracle SQL Recipes. You have in your hands a book of ready-made solutions to common problems encountered while writing SQL to run against an Oracle database. We’ve written this book for the person in a hurry who needs to solve a specific problem and then get on with the job. Each recipe addresses a specific problem and presents a solid, working solution to that problem. For those who are interested, each recipe also provides an extended discussion of the solution, and sometimes of alternative solutions. We’ve tailored the recipes to take you to the heights of a gourmet chef, at least as far as SQL for Oracle is concerned. Though we’ve split the recipes into logical chapters covering topics like data types or report generation, you should feel free to sample and use the recipes in any order, as well as in any combination.e